Reassessing the Matching Principle’s Relevance in Recognizing Staff Bonus Expenses in Corporate Tax Disputes - Kartiko, Nafis Dwi; Amrie Firmansyah; Abdul Al-Malik Al-Muluk (Siyasah Dusturiyah: State Law Review, 2025)
This study aims to analyze the application of the matching principle in the context of tax disputes related to the charging of employee bonus costs and to assess the appropriateness of recognizing these costs as deductible expenses based on positive tax law in Indonesia. This study uses a normative-dogmatic legal approach that aims to interpret, explain, and systematize positive legal norms governing the recognition of tax expenses in the application of the matching principle.  The results of the study show that the recognition of bonus expenses as accrued expenses better reflects economic substance than recognition as provisions, because the payment obligation has arisen from employee services that have been provided and can be reliably measured. This approach is in line with the substance over form principle, which places economic reality above administrative form. The court ruled that the obligation to pay bonuses had fulfilled the elements of certainty in terms of amount and recipient and was supported by evidence of payment realization and Article 21 tax deductions in the following year.